Pelatihan Manajemen Keuangan dan Pentingnya Pengelolaan Transaksi Keuangan pada Usaha Sparepart PC Second Jambi - Friska Artaria Sitanggang; Prayetno Agustinus Sitanggang; Henky Setiadi; Erny Melina; Jonner Simarmata; Christi Maharaja (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting national economic growth; however, many still face challenges in financial management practices. One of the primary issues identified in the Second Personal Computer (PC) Spare Parts business in Jambi City is the lack of systematic financial transaction recording, ineffective cash flow management, inadequate preparation of basic financial statements, and limited utilization of digital financial applications. These conditions make it difficult for business owners to monitor financial performance, evaluate business activities, and make appropriate managerial decisions. This community service program aimed to enhance the knowledge and skills of business owners in implementing effective and efficient financial management through both manual and digital financial recording practices. The implementation methods included preliminary observation, needs assessment, training sessions, practical exercises, mentoring, and interactive discussions. The training materials covered the fundamentals of financial management, transaction recording, cash flow management, preparation of basic financial statements, and the use of digital financial applications to support business operations. Program evaluation was conducted by observing participants' competencies before and after the activities. The results demonstrated significant improvements in participants' understanding of systematic financial management, their ability to record financial transactions and prepare basic financial reports, as well as increased awareness of utilizing digital financial applications to improve business performance. This program is expected to strengthen financial governance, improve the quality of managerial decision-making, and support the long-term sustainability and competitiveness of MSMEs.